KETERBUKAAN INFORMASI PEMERINTAH KOTA PROBOLINGGO MELALUI PENGGUNAAN AKUN INSTAGRAM @probolinggoimpressive - Maksin, Mastina; Fitria, Nurul Jannah Lailatul (DISCOURSE: Indonesian Journal of Social Studies and Education, 2024)
Public information disclosure continues to develop not only through official government websites, but the central and regional governments optimize the use of popular and trending social media. As in Probolinggo City, the Probolinggo City Government also uses social media in disseminating information and received an award as an Informative Public Agency at the Regency / City Level in East Java in the KI Award 2023. This is interesting to research. To find out the application of information disclosure in Probolinggo City through social media. This type of research applies a qualitative approach. Based on the results of research and analysis, the conclusion is that the quality of information services through Instagram @probolinggoimpressive social media owned by the Probolinggo City Government is included in the accurate, timely and relevant assessment. As well as information transparency through the @probolinggoimpressive account that can be received by the public well according to indicators of information speed; novelty (updating); interactivity; personalization; load capacity can be enlarged; connected with other sources (hyperlinks).